Correction: Unusual reversibility in molecular break-up of PAHs: the case of pentacene dehydrogenation on Ir(111). Issue 2 (8th January 2021) - Curcio, Davide; Sierda, Emil; Pozzo, Monica; Bignardi, Luca; Sbuelz, Luca; Lacovig, Paolo; Lizzit, Silvano; Alfè, Dario; Baraldi, Alessandro
Abstract : Correction for 'Unusual reversibility in molecular break-up of PAHs: the case of pentacene dehydrogenation on Ir(111)' by Davide Curcio et al., Chem. Sci., 2021, DOI: ; 10.1039/d0sc03734f .